PENINGKATAN PENGETAHUAN MASYARAKAT MENGENAI NUTRISI IBU HAMIL DI PUSKESMAS SUDIANG - Jusuf, Elizabet; Abidin, Nuraeni; Syahrir, Syahruni; Hartono, Eddy; Ajardiana; Tahir, Andi Mardiah; Aman, Abadi; Lotisna, Evelyn Natasya; Wijaya, Hambrian; Amelia, Kiki Rezki (Universitas Negeri Surabaya, 2026)
Chronic Energy Deficiency is still a problem in Indonesia. Lack of public awareness, particularly pregnant women, regarding proper nutritional adjustments in pregnant women needs attention from health workers. For this reason, the community service team of the Department of Obstetrics and Gynecology, Social Obstetrics and Gynecology Division, Faculty of Medicine, UNHAS in collaboration with the Sudiang Health Center held educational related to nutrition for pregnant women as a primary prevention effort and increased awareness about the importance of balanced nutrition in pregnant women. The purpose of the program is to increase public awareness, especially pregnant women, so that people understand the importance of balanced nutrition. The methods used in the implementation of these activities are lectures educational with lecture and question answer format. The evaluation results showed that there was a significant increase in the knowledge of pregnant women. Keywords: Nutrition, Pregnancy, Health Education